Undergraduate Medical students ‘attitudes towards learning communication skills - Jahan, F.; Norrish, M.; Said, N.; Abbas, Z. (Scientific Journal of Medical Science, 2014)
Communication is an essential skill for establishing physician-patient relationships and for effective functioning among health care professionals. This skill can be learnt effectively during the under graduate medical students’ training program and help students to practice in patient care efficiently. A cross-sectional study was carried out to assess the attitudes of medical students toward learning communication skills. All students in their first preclinical year and students in their final clinical year were asked to participate. Data was collected using the previously validated communication skills attitude scale (CSAS). The overall response rate was 79%. The broadly neutral attitude displayed by preclinical students was replaced in the final year clinical students by a significant increase in positive attitudes towards learning communication and a significant reduction in negative attitudes toward learning communication skills. Final year medical students have a more positive attitude towards learning communication skills. It is likely that this change in attitude is mediated by an increase in awareness of the utility of learning good communication skills through their regular daily clinical exposure to patients.